What are landfills, vermicomposting, recycling, and more... - Sharma, Richa (New Delhi The Energy Resources Institute, 2013)
Do you know that a chocolate wrapper cannot be recycled? Do you know that a plastic water bottle can lie in a garbage dump for up to five hundred years? Do you know that we can save the earth from becoming a giant dumping ground if we only practised the three Rs$1 (Breduce, reuse, and recycle? Learn how to keep the earth clean. It's our only home!s
Keywords: Landfills; Clean earth